Genome-wide identification and comparative analysis of CLE family in rapeseed and its diploid progenitors - Xie, Meili; Zhao, Chuanji; Song, Min; Xiang, Yang; Tong, Chaobo (Frontiers in Plant Science, 2022)
CLAVATA3/EMBRYO SURROUNDING REGION-RELATED (CLE) proteins belong to a small peptide family in plants. During plant development, CLE gene family members play a pivotal role in regulating cell-to-cell communication and stem cell maintenance. However, the evolutionary process and functional importance of CLEs are unclear in Brassicaceae. In this study, a total of 70 BnCLEs were identified in B. napus (2n=4x=38, AnCn): 32 from An subgenome, 36 from Cn subgenome and two from unanchored subgenome. Meanwhile, 29 BrCLEs and 32 BoCLEs genes were explored in B. rapa (2n=2x=20, Ar) and B. oleracea (2n=2x=18, Co). Phylogenetic analysis revealed that 163 CLEs derived from three Brassica species and Arabidopsis thaliana, can be divided into seven subfamilies. Homology and synteny analyses indicated whole genome triplication (WGT) and segmental duplication may be the major contributor for the expansion of CLEs family. In addition, RNA-Seq and qPCR analysis indicated that 19 and 16 BnCLEs were more highly expressed in immature seeds and roots than other tissues. Some CLE gene pairs exhibited different expression patterns in the same tissue, which indicated possible functional divergence. Furthermore, genetic variations and regional association mapping analysis indicated that twelve BnCLEs were potential genes for regulating important agronomic traits. This study provided valuable information to understand the molecular evolution and biological function of CLEs in B. napus and its diploid progenitors, which will be helpful for genetic improvement of high-yield breeding in B. napus.